A Rare Diagnosis of Caroli Syndrome in a Young Patient - Elaheh Karimzadeh‐Soureshjani; Farab Pourhasan; Pouria Ahmadi Simab; Sajjad Shojaei; Yasaman Mohammadian (Clinical Case Reports)
ABSTRACT Caroli syndrome is a rare but serious congenital disorder associated with portal hypertension and polycystic kidney disease. Early diagnosis via imaging, particularly MRCP, is crucial to prevent life‐threatening complications such as cholangitis and biliary cirrhosis. Timely intervention and close monitoring can significantly improve patient outcomes.